2011
DOI: 10.1002/hep.24395
|View full text |Cite
|
Sign up to set email alerts
|

Novel engineered targeted interferon-gamma blocks hepatic fibrogenesis in mice

Abstract: Liver fibrogenesis is a process tightly controlled by endogenous anti-and pro-fibrogenic factors. Interferon gamma (IFNc) is a potent antifibrogenic cytokine in vitro and might therefore represent a powerful therapeutic entity. However, its poor pharmacokinetics and adverse effects, due to the presence of IFNc receptors on nearly all cells, prevented its clinical application so far. We hypothesized that delivery of IFNc specifically to the disease-inducing cells and concurrently avoiding its binding to nontarg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 35 publications
10
89
0
Order By: Relevance
“…Therefore, systemic delivery of IFN-g results in immune cell and endothelial cell activation, flu-like symptoms, neurotropic effects, hyperlipidemia, elevated TNF-a and IL-6, CNS inflammation, and elevated triglycerides. Conspicuously, these side effects were almost completely absent following PEG-PPB-IFN-g administration (30), as also evidenced in this study by reduced brain MHC class II expression.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Therefore, systemic delivery of IFN-g results in immune cell and endothelial cell activation, flu-like symptoms, neurotropic effects, hyperlipidemia, elevated TNF-a and IL-6, CNS inflammation, and elevated triglycerides. Conspicuously, these side effects were almost completely absent following PEG-PPB-IFN-g administration (30), as also evidenced in this study by reduced brain MHC class II expression.…”
Section: Discussionsupporting
confidence: 84%
“…This region is able to modulate IFN-g-responsive genes through activation of the JAK/STAT (Janus kinase/ signal transducers and activators of transcription signaling pathway) pathway (65,66). We indeed previously showed activation of STAT1 by PEG-PPB-IFN-g (30). We therefore propose that PEG-PPB-IFN-g is taken up via PDGFRb, and the internalized construct next releases IFN-g or its metabolite intracellularly, which binds to IFN-g receptor 1 (IFN-gR1).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…21,22) for specific targeting to PDGFbR-expressing tumor stromal cells. Furthermore, we have shown that pPB-mediated targeting of IFNg to hepatic stellate cells, expressing high levels of PDGFbR during liver fibrosis, completely abolished advanced liver cirrhosis in mice (23). In this study, we delivered IFNg to stromal fibroblasts and pericytes using pPB-HSA carrier to impair angiogenesis thereby inhibiting the tumor growth, whereas avoiding IFNgmediated off-target effects.…”
Section: Introductionmentioning
confidence: 95%